2012
DOI: 10.1021/nl203389x
|View full text |Cite
|
Sign up to set email alerts
|

n-Type Nanostructured Thermoelectric Materials Prepared from Chemically Synthesized Ultrathin Bi2Te3 Nanoplates

Abstract: We herein report on the large-scale synthesis of ultrathin Bi(2)Te(3) nanoplates and subsequent spark plasma sintering to fabricate n-type nanostructured bulk thermoelectric materials. Bi(2)Te(3) nanoplates were synthesized by the reaction between bismuth thiolate and tri-n-octylphosphine telluride in oleylamine. The thickness of the nanoplates was ~1 nm, which corresponds to a single layer in Bi(2)Te(3) crystals. Bi(2)Te(3) nanostructured bulk materials were prepared by sintering of surfactant-removed Bi(2)Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(202 citation statements)
references
References 94 publications
10
192
0
Order By: Relevance
“…To improve the quality of nanoplates in solvothermal synthesis, various challenges must be overcome by modifying the experimental conditions. [24][25][26][27] To fabricate the ideal thermoelectric thin film, the nanoplates should be obtained in thin films. One of the most convenient methods of fabricating thin nanoplate films is the drop-casting technique using nanoplate inks because of its easy scalability, high deposition rate, and no requirement for vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the quality of nanoplates in solvothermal synthesis, various challenges must be overcome by modifying the experimental conditions. [24][25][26][27] To fabricate the ideal thermoelectric thin film, the nanoplates should be obtained in thin films. One of the most convenient methods of fabricating thin nanoplate films is the drop-casting technique using nanoplate inks because of its easy scalability, high deposition rate, and no requirement for vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 Te 3 hexagonal nanosheets are a typical representative of low-dimensional materials. Hyeon et al reported on ultrathin Bi 2 Te 3 nanosheets with ZT value of 0.62 at 400 K, which is one of the highest values among the reported ones based on chemically synthesized nanoparticles [17,18]. Current efforts toward fabricating Bi 2 Te 3 nanosheets are focused on hydrothermal reaction, solution-phase synthesis, and metal organic chemical vapor deposition (MOCVD).…”
Section: Introductionmentioning
confidence: 99%
“…The peak ZT of the bulk sample made from powders through the H-reduction is about 0.8 near the temperature of 80˚C. It is among the desired value of the high performance of thermoelectric material families of Bi 2 Te 3 alloys, for applications around 75˚C to 100˚C [18,19].…”
Section: Measurement Results and Discussionmentioning
confidence: 98%